2015
DOI: 10.1016/j.ajpath.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Stathmin-1 Expression Inhibits Trophoblast Proliferation and Invasion and Is Associated with Recurrent Miscarriage

Abstract: Fetal trophoblasts invade endometrium and establish a complex interaction with the maternal microenvironment during early pregnancy. However, the molecular mechanisms regulating trophoblast migration and invasion at the maternal-fetal interface remain poorly understood. Immunohistochemistry and immunoblotting have shown that stathmin-1 (STMN1) was down-regulated significantly in placental villi tissue and trophoblasts from patients with recurrent miscarriage. In vitro, overexpression of STMN1 promoted human tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 49 publications
8
47
0
Order By: Relevance
“…Villous cytotrophoblasts are progenitor cells that have strong proliferative ability and can fuse to form syncytiotrophoblasts or differentiate into extravillous trophoblasts. 3, 26, 27 Normal cytotrophoblast function is important for implantation, spiral artery remodeling and maternal–fetal communication. 3, 26, 28 Abnormal first-trimester trophoblast development and apoptosis is not only related with RM, but is also involved in many other pregnancy-related conditions such as preeclampsia and intrauterine growth restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Villous cytotrophoblasts are progenitor cells that have strong proliferative ability and can fuse to form syncytiotrophoblasts or differentiate into extravillous trophoblasts. 3, 26, 27 Normal cytotrophoblast function is important for implantation, spiral artery remodeling and maternal–fetal communication. 3, 26, 28 Abnormal first-trimester trophoblast development and apoptosis is not only related with RM, but is also involved in many other pregnancy-related conditions such as preeclampsia and intrauterine growth restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that, in HTR-8 cells, doxorubicin increased both mRNA and protein levels of TTP in a dose- and time-dependent manner. Previously, we had found that STMN1 expression was significantly decreased in uterine NK cells from CBA/J × DBA/2J mouse matings as compared with CBA/J × BALB/c mouse matings [42] and in patients with RSA [12], implying a link between STMN1 and p53/TTP signals.…”
Section: Discussionmentioning
confidence: 99%
“…We found that STMN1 was downregulated in the chorionic villi from patients with RSA. It is a trophoblast proliferation- and invasion-associated microtubule regulatory protein that participates in the pathogenesis of RSA [12]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sections were finally mounted with fluoroshield mounting medium with 4′,6‐diamidino‐2‐phenylindole (DAPI; Abcam) and then observed using a fluorescence microscope. For the BeWo cells, identification and localization of proteins were conducted using an immunofluorescence assay as previously reported 25. Rabbit anti‐adiponectin polyclonal antibody (1:50 dilution; Abcam) and E‐Cadherin rabbit monoclonal antibody (1:200 dilution; Cell Signaling Technology) were used as primary antibodies.…”
Section: Methodsmentioning
confidence: 99%